RESENSI BUKU : TheWorld of Maluku -Eastern Indonesia in Early Modern Period - FEBBY NANCY PATTY (KENOSIS: Jurnal Kajian Teologi, 2017)
LeonardÂ  Andaya adalah guru besar Sejarah Asia Tenggara di Universitas of Hawaii at Manoa. Ia menyelesaikan pendidikan sarjana di Yale University (1965) dan menyelesaikan pendidikan S2 dan S3 di Cornell University pada bidang sejarah Asia Tenggara. Beberapa karya buku yang dihasilkan di antaranya The Kingdom of Johor (1975); The Heritage of Arung Palakka : History of South Sulawesi (Celebes) in the Seventeenth Century (1981); History of Malaysia (1982); The World of Maluku: Eastern Indonesia in Early Modern Period (1993); Leave of the Same Tree: Trade and Etnicity in the Straits of Melaka (2008); History of Early Modern Southeast Asia, 1400-1830 (2015).